2010
DOI: 10.2169/internalmedicine.49.3360
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the Antimicrobial Susceptibility of Clinical Isolates of Pseudomonas aeruginosa from Respiratory Specimens and Antimicrobial Use Density (AUD) from 2005 through 2008

Abstract: Objective To examine the relation between annual trends in the antimicrobial susceptibility of Pseudomonas aeruginosa and drug usage, we compared annual changes in the susceptibility rates of P. aeruginosa clinical isolates during a 4-year period and annual trends in the overall usage of antimicrobials during the same period. Methods We studied annual trends in MIC90/MIC50, antimicrobial use density (AUD), and antimicrobial susceptibility rates based on clinical breakpoints for 150 strains of P. aeruginosa iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…The ceftazidime concentration at the end of each dwell depends on the serum concentration of ceftazidime at each time point and the number of dwell hours. The serum levels at the end of the 24 h were above the upper limit of susceptibility (MIC, 8 g/ml) for ceftazidime against nosocomial pathogens such as Enterobacteriaceae or P. aeruginosa (5). The mean dialysate concentration at the end of each dwell exceeded two times the MIC against susceptible organisms.…”
Section: Discussionmentioning
confidence: 97%
“…The ceftazidime concentration at the end of each dwell depends on the serum concentration of ceftazidime at each time point and the number of dwell hours. The serum levels at the end of the 24 h were above the upper limit of susceptibility (MIC, 8 g/ml) for ceftazidime against nosocomial pathogens such as Enterobacteriaceae or P. aeruginosa (5). The mean dialysate concentration at the end of each dwell exceeded two times the MIC against susceptible organisms.…”
Section: Discussionmentioning
confidence: 97%
“…24,25 Restrictions or decreases in the use of carbapenems have been responsible for reductions in the rates of carbapenem-resistant P. aeruginosa infection. 26,27 However, there are conflicting results concerning ertapenem use and improvement in the rates of carbapenem-resistant P. aeruginosa infection. [4][5][6][7] Goff et al 4 concluded that susceptibility to imipenem in P. aeruginosa did not change after the continuous use of ertapenem for 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…8 Conversely, decreased use of carbapenem following antibiotic restriction and education programs has been associated with reduced carbapenem resistance in Pseudomonas aeruginosa and Acinetobacter sp. [9][10][11][12] A relationship between use of carbapenems and resistance in Enterobacteriaceae was not demonstrated in observational studies conducted in areas where prevalence of resistance was low. 7,[12][13][14] However, meropenem consumption was significantly correlated to resistance rates in E coli and Klebsiella pneumoniae where prevalence was high.…”
Section: Introductionmentioning
confidence: 99%